Some theoretical and methodological insight into the jigsaw puzzle of ethnocartography - Vince Pallua Jelka; International Ethnography network : Conference of the SIEF's : [International Society for Ethnology and Folklore] (16.) (2010) (Szeged) (2012)
The immediate impulse for this paper came from the author’s empirical involvement with the topics concerning “social culture” while dealing with ethnocartography used in a historically oriented ethnology. This auxiliary heuristic technique is being observed as the jigsaw puzzle of the “old” and the “new” theoretical commitments in Croatian ethnology in the 1970s and 1980s. Although ethnological cartography (not having the methodological power to holistically depict culture, but to particulate/atomize it) represents only one ofthe possible ways of gaining knowledge in ethnological research, on the basis of two main thematic wholes -the concept ofhistory and the object ofresearch -the author’s aim is to defend those principal characteristics of ethnocartography deemed indispensable, the ones that sustain and defend its relevance and existence.
Keywords: Társadalomtudományok; Szociológia